Substantiation of the need to implement simulation training for dental students based on the analysis of the activities of the Stomatological Medical Center at O. Bogomolets National Medical University - Chopchik , Vitaliy (The Ukrainian Scientific Medical Youth Journal, 2023)
the article analyzes the existing problems of practical training of dental students at the clinical bases of specialized departments in the modern conditions of the health care system reforms, as well as the impact of the COVID-19 pandemic and armed aggression of the russian federation, and also substantiates the feasibility of simulation training for students of dental faculties. The research is based on the study of statistical materials of the Stomatological Medical Center in O. Bogomolets NMU (SMC), the results of an anonymous survey of graduates of the Dental Faculty, interns and doctors who underwent post-graduate training at the SMC. A tendency to a significant decrease in the number of applications for dental care to the university dental clinic has been demonstrated with an increase in the proportion of patients receiving paid dental services who were excluded from the educational process. Such tendency limits the possibility of acquiring practical skills directly during the clinical diagnostics and treatment of patients. Thus, the total number of patient visits to the SMC was: in 2012–257,115 patients, in 2019–181,507 patients, and in 2022–101,471 patients. Of these, 94,416 patients were admitted as part of the educational process in 2012, 56,693 in 2019, and 18,382 patients in 2022. A significant drop in the number of patients who visited the Stomatological Medical Center, a relatively constant number of dental students at O. Bogomolets NMU and the realities of the past three years have led to the emergence of certain restrictions and reduced opportunities for practical training of future dentists. The presented data made it possible to calculate the average number of patients per student of medical and dental education per year, which was 52.57 in 2012, 25.85 in 2019, and only 9.22 people in 2022. The limited possibility of training with the involvement of thematic patients is a reason to revise the approaches to the practical training for dentists with the expansion of the use of simulation equipment with the possibility of computer control of practicing skills. The results of the anonymous survey also confirm the need to improve the effectiveness of the practical training of dental students and interns, in particular through the introduction of new forms of training, such as simulation training. Advantages and disadvantages of this form of practical training under different conditions of organization of the educational process are discussed.